The honesty of thinking: reflections on critical thinking in Nietzsche's middle period and the later Heidegger - Rasmus-Vorrath, J; Jack Kendrick Rasmus-Vorrath (2014)
This dissertation engages with contemporary interpretations of Nietzsche and Heidegger on the issue of self-knowing with respect to the notions of honesty and authenticity. Accounting for the two philosophers' developing conceptions of these notions allows a response to interpreters who conceive the activity of self-knowing as a primarily personal problem. The alternative accounts proposed take as a point of departure transitional texts that reveal both thinkers to be engaged in processes of revision. The reading of honesty in Chapters 1 and 2 revolves around Nietzsche's groundwork on prejudice in Morgenröthe (1880-81), where he first problematizes the moral-historical forces entailed in actuating the 'will to truth'. The reading of authenticity in Chapters 3 and 4 revolves around Heidegger's lectures on what motivates one's thinking in Was heißt Denken? (1951-52). The lectures call into question his previous formal suppositions on what calls forth one's 'will-to-have-a-conscience', in an interpretation of Parmenides on the issue of thought's linguistic determination, discussed further in the context of Unterwegs zur Sprache (1950-59). Chapter 5 shows how Heidegger's confrontation with Nietzsche contributed to his ongoing revisions to the notion of authenticity, and to the attending conceptions of critique and its authority. Particular attention is given to the specific purposes to which distinct Nietzschean foils are put near the confrontation's beginning--in Heidegger's lectures on Nietzsche's second Unzeitgemässe Betrachtung (1938), and in the monograph entitled Besinnung (1939) which they prepare--and near its end, in the interpretation of Also Sprach Zarathustra (1883-85) presented in the first half of Was heißt Denken? Chapter 6 recapitulates the developments traced from the vantage point of the retrospective texts Die Zollikoner Seminare (1959-72) and the fifth Book of Die fröhliche Wissenschaft (1887). Closing remarks are made in relation to recent empirical research on the socio-environmental structures involved in determining self-identity.